La adfinitas de las lenguas aquitana e ibérica (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In those aspects that can be documented or meridianly reconstructed the Aquitanian and Iberian languages would present a significantly considerable number of convergences. The unavoidable geo-glotological interpretation of this information suggests that this linguistic affinity must have been translated, in a prehistoric times, into some degree of adfinitas or spatial contact between both types of speeches.